The TMEM106B T186S coding variant increases neurite arborization and synaptic density in primary hippocampal neurons - Nguyen, Quynh; Wood, Caleb A.; Kim, Peter J.; Jankowsky, Joanna L. (Frontiers in Neuroscience, 2023)
Lysosomal protein TMEM106B was identified as a risk modifier of multiple dementias including FTD and AD. The gene comes in two major haplotypes, one associated with disease risk, and by comparison, the other with protection. Only one coding polymorphism distinguishes the alleles, a threonine-to-serine substitution at residue 185 (186 in mouse). Subjects carrying the protective allele display brain transcriptional signatures of neuronal resilience, including elevated expression of synaptic modules and increased neuronal gene expression suggestive of neuronal preservation. Despite this background, the field still hasn't resolved whether the coding variant is biologically meaningful, and if so, whether it has any particular effect on neuronal phenotypes. Here we tested for transcriptional effects of TMEM106B manipulation in T186S knock-in and constitutive deletion mice. Cortical mRNA signatures in T186S mice were enriched for genes associated with synaptic function and axon outgrowth, prompting us to study neuronal development in greater detail. Dendritic arbors of T186S hippocampal neurons were more highly branched and had greater spine density than wild-type controls. Our work suggests that the protective TMEM106B haplotype, acting through its lone coding variant, may contribute to disease resilience by supporting stronger neuronal networks capable of withstanding greater damage before succumbing to cognitive decline.